An Examination of the Frequency of Paravascular Defects and Epiretinal Membranes in Eyes With Early Glaucoma Using En-face Slab OCT Images. Issue 3 (March 2019) - Mavrommatis, Maria A.; De Cuir, Nicole; Reynaud, Juan; De Moraes, Carlos G.; Xin, Daiyan; Rajshekhar, Rashmi; Liebmann, Jeffrey M.; Ritch, Robert; Fortune, Brad; Hood, Donald C.
Abstract : Purpose: To examine the frequency of paravascular defects (PDs) and macular epiretinal membranes (ERMs) in eyes categorized as having mild glaucoma or glaucoma suspect using en-face slab analysis of optical coherence tomography (OCT) scans. Materials and Methods: Fifty-seven glaucomatous eyes, 44 low-risk suspect eyes, and 101 healthy control eyes were included in the study. The 101 glaucomatous and suspect eyes had a mean deviation better than −6 dB on the 24-2 visual field, and a spherical refractive error between±6 D or axial length <26.5 mm. Two OCT-graders masked to eye classification identified ERMs and PDs on en-face slab images of the macula and peripapillary retina using horizontal B-scans and derived vertical B-scans. Results: Glaucomatous eyes had a significantly higher number of PDs and ERMs than healthy controls (PD, P <0.001; ERM, P =0.046) and low-risk glaucoma suspects (PD, P =0.004; ERM, P =0.043). PDs and/or ERMs were present in 16 of 57 (28.1%) glaucomatous eyes, 2 of 44 (4.5%) suspect eyes, and 3 of 101 (3.0%) control eyes. Further, PDs were present in 11 of the 57 (19.3%) glaucomatous eyes, 1 of the 44 (2.3%) suspect eyes and 0 of the 101 (0%) control eyes, ERMs were seen in 7 of the 57 (12.3%) glaucomatous eyes, 1 of the 44 (2.3%) suspects, and 3 of the 101 (3.0%) control eyes. Conclusions: Eyes with early glaucoma have a higher frequency of PDs and ERMs than suspects or controls and exhibit PDs even in the absence of ERMs or high myopia.